Urinary Bladder Cancer in Egypt: Are There Gender Differences in Its Histopathological Presentation? - Fiorina Kyritsi; Christopher A. Loffredo; Yun-Ling Zheng; George Philips; Sania Amr (Advances in Urology)
We investigated gender differences in the histopathologic presentation of bladder cancer cases in Egypt, where both urothelial cell carcinoma (UC) and squamous cell carcinoma (SCC) types are highly prevalent. We used logistic regression to estimate the unadjusted (OR) and adjusted odds ratio (AOR) and 95% confidence interval (CI) of the associations between gender and different histopathologic and sociodemographic parameters of 2,186 confirmed cases of primary bladder cancer (1,775 males and 411 females; 784 SCC and 1,402 UC). There were no statistically significant gender differences in tumor grade, stage, mucosal ulcer, or inflammatory cystitis, regardless of the cancer type, but men were less likely than women to have undergone cystectomy with pelvic lymphadenectomy. Having Schistosoma haematobium (SH) ova in the bladder tissue was significantly associated with male gender in the fully adjusted model of either SCC (AOR (95% CI) = 2.12 (1.15–3.89)) or UC cases (3.78 (1.89–7.55)). Compared to females, male cases were significantly older at time of diagnosis and smokers. In Egypt, regardless of the type of bladder cancer (SCC or UC), male more than female cases had evidence of SH infection, but not other histopathologic differences, in bladder tissue specimens.